Study Of Socio-Demographic Profile of Burn Cases Admitted in Shri Chhatrapati Shivaji Maharaj General Hospital, Solapur - Haralkar , Santosh Jagannath; Tapare , Vinay S; Rayate , Madhavi V (National Journal of Community Medicine, 2011)
The problem of burn in developing countries like India is more due to various socio-cultural factors present in the country. The study was aimed to find the distribution, determinants, outcome and psychological effect of burns. The present hospital based descriptive study was carried out in surgery ward of Shri Chhatrapati Shivaji Maharaj, General Hospital Solapur, to know socio – demographic profile, duration of stay and outcome of burn. All cases of burns admitted in Hospital during study period (September 2000 to August 2001) were the study subjects. More than half were in the age group between 21 and 40 years. More than two third were females. Rural patients outnumbered urban patients. Majority of patients were unemployed and among unemployed majority of patients were housewives. 40% patients were literate. Majority of the cases were from class IV (Upper Lower) socioeconomic group. Majority of patients (37.78%) were admitted during winter season. Maximum number of burns occurred between 5pm and 11 pm. Majority of burns (97.56%) took place at home. 79.33% of burns were accidental. 36% patients had hospital stay less than one day. Among 450 cases, 65.78% died, 16.44% were discharged against medical advice.